2013
DOI: 10.1152/japplphysiol.00760.2012
|View full text |Cite
|
Sign up to set email alerts
|

High- versus moderate-intensity aerobic exercise training effects on skeletal muscle of infarcted rats

Abstract: Moreira JB, Bechara LR, Bozi LH, Jannig PR, Monteiro AW, Dourado PM, Wisløff U, Brum PC. High-versus moderate-intensity aerobic exercise training effects on skeletal muscle of infarcted rats. J Appl Physiol 114: 1029 -1041, 2013. First published February 21, 2013 doi:10.1152/japplphysiol.00760.2012.-Poor skeletal muscle performance was shown to strongly predict mortality and long-term prognosis in a variety of diseases, including heart failure (HF). Despite the known benefits of aerobic exercise training (AET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
87
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 65 publications
15
87
2
13
Order By: Relevance
“…Current evidence demonstrates that regular physical training not only improves exercise capacity and oxygen uptake in patients with heart failure, but also attenuates left-ventricular dilatation and abnormal cardiac remodeling [6]. In addition, training is associated with improved endothelial function and left-ventricular ejection fraction and reduced hospital readmissions in patients with heart failure [7] .Consistently, studies on different models of cardiac injury have indicated that exercise promotes a broad range of effects beneficial to the heart, such as the attenuation of calcium imbalance, renin-angiotensin and sympathetic nervous system activation, mitochondrial dysfunction, and oxidative stress [8,9]. In recent years, inspiratory muscle training has demonstrated a positive impact on ventilatory efficiency, respiratory muscle strength, peak oxygen consumption, and functional capacity in different types of cardiac dysfunction [10].…”
mentioning
confidence: 99%
“…Current evidence demonstrates that regular physical training not only improves exercise capacity and oxygen uptake in patients with heart failure, but also attenuates left-ventricular dilatation and abnormal cardiac remodeling [6]. In addition, training is associated with improved endothelial function and left-ventricular ejection fraction and reduced hospital readmissions in patients with heart failure [7] .Consistently, studies on different models of cardiac injury have indicated that exercise promotes a broad range of effects beneficial to the heart, such as the attenuation of calcium imbalance, renin-angiotensin and sympathetic nervous system activation, mitochondrial dysfunction, and oxidative stress [8,9]. In recent years, inspiratory muscle training has demonstrated a positive impact on ventilatory efficiency, respiratory muscle strength, peak oxygen consumption, and functional capacity in different types of cardiac dysfunction [10].…”
mentioning
confidence: 99%
“…Atrogin-1/MAFbx também está aumentada na musculatura esquelética de animais com IC, refletindo em maior atividade do proteassoma, o que pode ter contribuído para atrofia muscular (Cunha et al, 2012;Moreira et al, 2013).…”
Section: Um Dos Fatores De Crescimento Mais Estudados é O Igf-1 (Insuunclassified
“…A disfunção cardíaca associada aos sintomas de edema pulmonar e intolerância ao esforço físico são indicativos da presença de IC nos animais infartados (Lucas et al, 2000). Todas essas alterações corroboram com resultados anteriores do nosso e de outros laboratórios (Ferreira et al, 2011;Moreira et al, 2013;Schulze et al, 2003;Tsutsui et al, 2001), e indicam que a cirurgia de IM em ratos é eficaz em promover IC e mimetizar sintomas presentes em humanos com esta doença.…”
Section: Caracterização Fenotípica Do Modelo Experimental De Insuficiunclassified
See 2 more Smart Citations